Pengaruh Gaya Kepemimpinan, Kompetensi dan Motivasi Terhadap Kinerja Personel Biro SDM Polda Sulsel - Firman Ridwan; Aryati Arfah; Muhammad Akhsan Tenrisau (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
Abstract This study aims to: (1) examine and analyze the effect of leadership style on personnel performance; (2) examine and analyze the effect of competence on personnel performance; (3) examine and analyze the effect of work motivation on personnel performance; and (4) examine and analyze the simultaneous effect of leadership style, competence, and work motivation on personnel performance. This study uses primary data collected through a survey of 100 personnel from the Human Resources Bureau of the South Sulawesi Regional Police (Polda) in 2026, employing a full sampling method. The survey was conducted from February to April 2026. Data were analyzed using SPSS (Statistical Package for the Social Sciences). The results indicate that: (1) leadership style has a positive and significant effect on personnel performance; (2) competence has a positive and significant effect on personnel performance; (3) work motivation has a positive and significant effect on personnel performance; and (4) leadership style, competence, and work motivation simultaneously have a significant contribution to improving personnel performance. These findings imply that personnel performance is strongly influenced by the quality of leadership style, the level of competence, and work motivation. The more effective the leadership in managing subordinates, the higher the competence of personnel, and the stronger the work motivation, the better the resulting performance. Therefore, these three factors are key determinants in achieving organizational success. Research recommendations are as follows: (1) for leaders, it is recommended to continuously develop effective leadership styles, including decision-making ability, communication, motivation, supervision of subordinates, responsibility, and emotional control to maintain optimal personnel performance; (2) for personnel, it is expected to enhance competence through the development of character, knowledge, skills, and work motivation to support better performance achievement; and (3) for organizations, it is recommended to pay attention to personnel motivation by ensuring the fulfillment of physiological needs, safety, social needs, esteem, and self-actualization, in order to create a conducive and productive work environment. Keywords: Leadership Style, Competence, Work Motivation, Personnel Performance.